Hydrophobic effects are dominant over secondary orbital interactions for a simple Diels-Alder reaction in salt solutions - Sarma, D.; Kumar, Anil (Organic Letters, 2006)
The stereoselectivity ratios for a Diels-Alder reaction between cyclopentadiene with methyl trans-crotonate carried out in salt solutions demonstrate the dominance of hydrophobic effects over secondary orbital interactions.

Hydrophobic effects in a simple Diels-Alder reaction in water - Sarma, D.; Pawar, S. S.; Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron Letters, 2006)
The endolexo ratio for a simple Diels-Alder reaction carried out in water has been used to argue that hydrophobic effects can dominate the geometries of the transition states. (c) 2006 Elsevier Ltd. All rights reserved.

Homogeneous nucleation temperatures in aqueous mixed salt solutions - Kumar, Anil (Journal of Physical Chemistry B, 2007)
This is the first report on the measurement of homogeneous nucleation temperature, T-H, in the presence of aqueous mixed salt systems of varying compositions and ionic strengths. The T-H,T-m (T-H value in aqueous mixed salt system) data for these systems have been analyzed in terms of a simple empirical equation. The T-H.m. values in simple aqueous mixed salts like NaCl-KCl can be approximated by linear summation of the products of ionic strength fraction and the T-H values of pure salt solutions at the same ionic strength as that of the mixture. The empirical parameter, q(0), indicating ionic interaction is related to the viscosity B-coefficients. The T-H.m data, though correlated on the basis of the B-coefficients also depends upon the mixing of two ions of like charges. Further, a linear correlation exists between the q(0) parameter and self-diffusion coefficient, D-0, of the ionic solute. The q(0) parameter is also well correlated with the rotational correlation time, T-c(h)/T-c(0) of the ionic species involved in the mixtures. It is possible to compute T-H,T-m for the salt mixtures with no common ions from the knowledge of the T-H,T-m values of the salt mixtures with common ions.

High viscosity of ionic liquids causes rate retardation of Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Science China-Chemistry, 2012)
Second order rate constants, k (2) have been determined for three bi-molecular Diels-Alder reactions to demonstrate that the high viscosity of ionic liquids can be a detrimental property in carrying out Diels-Alder reactions, if ionic liquids are employed as solvent media. It is possible to enhance the reaction rates of the reaction if a co-solvent is mixed in pure ionic liquid used as a solvent.
Keywords: Diels-Alder reactions; ionic liquids; kinetics; viscosity

Hydrophobic and hydrophilic balance and its effect on mesophase behaviour in hydroxyalkyl ethers of methyl glucopyranoside - Singh, Madan K.; Xu, Rui; Moebs, Sylvie; Kumar, Anil; Queneau, Yves; Cowling, Stephen J.; Goodby, John W. (Chemistry-A European Journal, 2013)
Four series of monosubstituted methyl -D-glucopyranoside hydroxyalkyl ethers were prepared and their thermotropic and lyotropic self-organising properties were investigated in terms of the hydrophobichydrophilic balance with respect to their molecular structures. The results obtained lead us to a new understanding of the forces that drive the formation of condensed soft-matter phases.
Keywords: carbohydrates; liquid crystals; mesophases; Self-assembly; soft matter